2023
DOI: 10.3390/su15075852
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inclusiveness and Female Representation on the Board of Directors of the Benefit Company Model: Evidence from Italy

Abstract: This study aims to analyse whether firms adopting the institutional and organizational model of a benefit company (BC) increase the appointment of women to their board of directors (BoD) by applying the theoretical models of reputation management and resource dependence theory. A sample of 354 Italian firms adopting the BC model and a control group of 600 firms over the period of 2009–2018 were analysed. A fractional regression probit model was used to analyse the effect of the institutional form of the BC on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Evidence from medicine and other fields has shown that gender diversity results in better decision making and outcomes. 1 , 2 , 3 Furthermore, gender equity has been shown to result in more effective health policy development and patient care. 4 , 5 Pediatric cardiology is a unique field, with origins in the brilliant insight and collaboration of Dr Maude Abbott, a pathologist and Dr Helen Taussig, a clinician and educator who started the first pediatric cardiology fellowship‐training program.…”
mentioning
confidence: 99%
“…Evidence from medicine and other fields has shown that gender diversity results in better decision making and outcomes. 1 , 2 , 3 Furthermore, gender equity has been shown to result in more effective health policy development and patient care. 4 , 5 Pediatric cardiology is a unique field, with origins in the brilliant insight and collaboration of Dr Maude Abbott, a pathologist and Dr Helen Taussig, a clinician and educator who started the first pediatric cardiology fellowship‐training program.…”
mentioning
confidence: 99%